STEREOTIP GENDER PADA BUDAYA PATRIARKI INDONESIA SEBAGAI HAMBATAN PEKERJA PEREMPUAN BERPERAN GANDA - Sutarman, Tifanny; Hanifatusholihah, Hanifatusholihah; Panggabean, Hana; Marta, Rustono Farady; Kurniawati, Laurencia Steffanie Mega Wijaya (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Women have their own challenges facing gender stereotypes in the workplace. For Indonesian people who are generally close to a patriarchal culture, men and women are considered to have different roles and natures. The assumption of society that is created from the existence of gender stereotypes makes women have limitations in getting the same opportunities and rights as men in the public sphere. This gender stereotype later becomes an invisible barrier for working women or called as the glass ceiling. The glass ceiling that women get from the existence of gender stereotypes is divided into two, self-concept as an internal factor and patriarchal culture and multiple role as an external factor. The glass ceiling effect in companies has an impact on the tendency of companies to choose men for top positions, the practices of recruitment of gender-based recruitment, the existence of behavior and culture resulting from gender stereotypes that underestimate women's abilities, and the strengthening formation of cultural structures within a company based on gender roles. This paper is a conceptual idea that uses the literature review method to determine the extent to which gender stereotypes in Indonesia are seen as creating barriers for female workers.Keywords: gender stereotypes, glass ceiling, multiple roles, patriarchal culture, self-conceptPerempuan memiliki tantangan tersendiri menghadapi stereotip gender dalam lingkungan pekerjaan. Bagi masyarakat Indonesia yang secara umum erat dengan budaya patriarki, laki-laki dan perempuan dinilai memiliki peran dan kodrat yang berbeda-beda. Anggapan masyarakat yang tercipta dari adanya stereotip gender membuat perempuan memiliki keterbatasan dalam mendapatkan kesempatan dan hak yang sama dengan laki-laki di ranah publik. Stereotip gender ini nantinya menjadi hambatan yang tidak terlihat bagi perempuan pekerja atau dalam istilah disebut dengan glass ceiling. Glass ceiling yang didapatkan perempuan dari adanya stereotip gender terbagi menjadi dua yaitu konsep diri sebagai faktor internal dan budaya patriarki serta peran ganda sebagai faktor eksternal. Efek glass ceiling dalam perusahaan dapat berdampak pada kecenderungan perusahaan dalam memilih laki-laki untuk posisi-posisi atas, terjadinya praktek rekrutmen yang berbasis gender, adanya perilaku dan budaya hasil dari stereotip gender yang menyepelekan kemampuan perempuan, dan semakin kuatnya pembentukan struktur budaya di dalam sebuah perusahaan dengan berlandaskan pada peran gender. Tulisan ini merupakan gagasan konseptual yang menggunakan metode kajian literatur untuk mengetahui sejauh mana stereotip gender di Indonesia dipandang bisa menghasilkan hambatan bagi pekerja perempuan. Kata Kunci : stereotip gender, glass ceiling, peran ganda, budaya patriarki, konsep diri.